2022
DOI: 10.5194/essd-14-1193-2022
|View full text |Cite
|
Sign up to set email alerts
|

A global land aerosol fine-mode fraction dataset (2001–2020) retrieved from MODIS using hybrid physical and deep learning approaches

Abstract: Abstract. The aerosol fine-mode fraction (FMF) is valuable for discriminating natural aerosols from anthropogenic ones. However, most current satellite-based FMF products are highly unreliable over land. Here, we developed a new satellite-based global land daily FMF dataset (Phy-DL FMF) by synergizing the advantages of physical and deep learning methods at a 1∘ spatial resolution covering the period from 2001 to 2020. The Phy-DL FMF dataset is comparable to Aerosol Robotic Network (AERONET) measurements, based… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 82 publications
1
15
1
Order By: Relevance
“…Since pollution forecasting involves a high-dimensional parameter space, with partial amounts of data, the ability of deep learning to integrate data and physics models could provide suitable architecture for highly accurate and efficient forecasting models. Indeed, preliminary work in this emerging field has been carried out using the outputs of the physical model as the inputs for the deep-learning model, for the purpose of predicting fine-mode fractions (FMF) of aerosols over land, and achieving an accuracy higher than current methods [124]. The authors found that, compared with more traditional physical-based and deep-learning-based FMF results, the their PINN was more accurate at predicting FMF values over five land types (e.g., barren land, croplands, forests, grasslands and urban area).…”
Section: Physics Informed Modelsmentioning
confidence: 99%
“…Since pollution forecasting involves a high-dimensional parameter space, with partial amounts of data, the ability of deep learning to integrate data and physics models could provide suitable architecture for highly accurate and efficient forecasting models. Indeed, preliminary work in this emerging field has been carried out using the outputs of the physical model as the inputs for the deep-learning model, for the purpose of predicting fine-mode fractions (FMF) of aerosols over land, and achieving an accuracy higher than current methods [124]. The authors found that, compared with more traditional physical-based and deep-learning-based FMF results, the their PINN was more accurate at predicting FMF values over five land types (e.g., barren land, croplands, forests, grasslands and urban area).…”
Section: Physics Informed Modelsmentioning
confidence: 99%
“…Environmental covariates selected in this study contain 12 covariates in three categories (meteorology, surface information, and topography). Covariates are selected based on two criteria: first, each variable is considered important to AOD and has a vital influence on AOD formation, accumulation and migration process, referring to existing research and expert experience (Zhao et al, 2019;Chen et al, 2020;Yan et al, 2022); the second, the data is released to the public for free, which means that the data set is freely available on the national or global scale (Li et al, 2020). The detailed information is listed in Tab.1.…”
Section: Environmental Covariatesmentioning
confidence: 99%
“…The AERONET AOD data have a low uncertainty (0.01-0.02) and are considered the highest accuracy AOD data available; these data are widely used as a reference in RS AOD product validations (Almazroui, 2019). In this study, data from a total of 12 AERONET sites in northwest China were selected, most of which were from the third version of the level 2.0 AERONET AOD, except for the Mt_WLG station data (Level 1.5) (Yan et al, 2022;Giles et al, 2019). Related information about these AERONET sites is available in Table S2 and Fig.…”
Section: Aeronet Datamentioning
confidence: 99%
“…The environmental covariates selected in this study comprised 12 covariates in three categories (meteorological parameters, surface properties, and terrain factors). The covariates were selected based on two criteria: first, each variable had to be considered important to the AOD and to have a vital influence on the AOD formation, accumulation, and migration processes, referring to existing research and expert experience Chen et al, 2020;Yan et al, 2022); and second, the data must be freely released to the public, meaning the datasets must be freely available on the national or global scale (Li et al, 2020). Detailed information on these covariates is listed in Table 1.…”
Section: Environmental Covariatesmentioning
confidence: 99%
See 1 more Smart Citation